Web-Based Simple Multi Attribute Rating Technique for Employee Performance Evaluation: Penerapan Simple Multi Attribute Rating Technique Berbasis Web untuk Evaluasi Kinerja Pegawai - Siregar, M. Fredyansyah; Ardian, Zalfie; Fhonna, Rizky Putra (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Employee performance evaluation in government institutions often lacks objectivity and consistency, causing unequal treatment and management inefficiency. Specific background: The Lhokseumawe District Prosecutor’s Office required a structured evaluation system for honorary employees to ensure transparent and fair assessments. Knowledge gap: Few studies have applied the Simple Multi Attribute Rating Technique in government-based performance evaluation systems. Aims: This study aimed to design and implement a web-based evaluation system using the Simple Multi Attribute Rating Technique to support accurate and accountable decision-making. Results: The developed system reduced evaluator subjectivity, ensured consistent weighting of criteria, and produced objective evaluation results. Usability testing showed an average System Usability Scale score of 80.92, categorized as “Good.” Novelty: This study presents the first integration of this method into a prosecutorial work environment. Implications: The system contributes to modernization in public human resource management by promoting transparency, fairness, and efficiency in employee evaluation and decision-making. Highlights Structured evaluation system improves fairness and transparency Consistent weighting ensures objective performance assessment Web-based system enhances efficiency and accountability Keywords Employee Performance Evaluation, Simple Multi Attribute Rating Technique, Web-Based System, Public Institution, Accountability